Social realist proposals for the modernization of the Latin American state - Infante, Benjamín (Política. Revista de Ciencia Política, 2023)
This article analyses the challenges of modernising the Latin American state from the perspective of social realism and proposes two mechanisms for implementing change. To do so, it historically situates the problem of Latin American state modernisation and characterises the relational trends between civil society and the state. From this initial analysis, he concludes that there is a lack of political representation due to the existence of an incompatible relationship between the vested interests that control the state and those of organised civil society. The mechanisms proposed in this article to bridge this gap are aimed at increasing the state's capacity to fulfil the public functions required by the general interest: a first mechanism acts correctively on the economic system and has as its protagonists social movements and corporate groups already constituted in civil society; and a second mechanism acts proactively, ideationally and structurally diversifying primary groups, currently not constituted as interest groups, to manage areas of the social sphere. On reflection, we believe that the emergence of a contingency that poses the challenge of strategic renewal at the national level could alter the incompatibility between state and civil society, thus opening up the opportunity to build new agencies around the general interests that underpin our political community.